NAIRA ABUSE BY NIGERIAN CELEBRITIES: PERSPECTIVES OF AE FUNAI STUDENTS ON BOBRISKY AND CUBANA CHIEF PRIEST CASES - Ononuju Nwankiti, Chukwuemeka; Cosmas Nwoga, Chibuzor; Rose Chime-Nganya, Chioma; Obin Obin, Ogban; Lynda Ngwu, Ogonnaya (African Journal of Social and Behavioural Sciences, 2024)
This study examines the misuse of the Nigerian Naira on social media by celebrities, focusing on Bobrisky and Cubana Chief Priest. Utilising a descriptive survey design, 374 AE-FUNAI students were surveyed using the Taro Yamane method. Celebrity Endorsement theory was adopted to explain the behavioural pattern, while three research questions and objectives guided the study. Data was analysed using percentages and a 4-point Likert scale mean value method. Findings revealed that respondents are aware of naira abuse on social media. Naira abuse has significant negative socio-cultural and economic impacts if left unchecked. Respondents acknowledged whistle-blowing on violators of naira abuse on social media as a definite approach to curbing misuse of naira, amongst other stricter regulatory measures. Recommendations include enhanced collaboration between the CBN, NOA, and social media platforms to address this issue, teamwork with celebrities to generate awareness against misuse of the naira, encouraging Federal lawmakers to make more stringent laws on misuse of the naira, the increased presence of EFCC in Nigerian universities to checkmate the excesses of students and Cultural orientation by parents to instil a sense of contentment and respect for honest labour and genuine jobs.